2010
DOI: 10.1029/2009wr008016
|View full text |Cite
|
Sign up to set email alerts
|

Spatial‐temporal variability of soil moisture and its estimation across scales

Abstract: The soil moisture is a quantity of paramount importance in the study of hydrologic phenomena and soil‐atmosphere interaction. Because of its high spatial and temporal variability, the soil moisture monitoring scheme was investigated here both for soil moisture retrieval by remote sensing and in view of the use of soil moisture data in rainfall‐runoff modeling. To this end, by using a portable Time Domain Reflectometer, a sequence of 35 measurement days were carried out within a single year in seven fields loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
274
10
2

Year Published

2013
2013
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 383 publications
(311 citation statements)
references
References 53 publications
25
274
10
2
Order By: Relevance
“…For the Pósa Valley, the Number of Representative Stations (NRS) did not significantly changed with increasing soil moisture content (Figure 8). This finding contradicts the conclusion of [38]. The value of NRS varied between 2 and 30 per 100 km 2 in the Pósa Valley when AE was changed to values between 0.5 and 2% (Figure 8).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…For the Pósa Valley, the Number of Representative Stations (NRS) did not significantly changed with increasing soil moisture content (Figure 8). This finding contradicts the conclusion of [38]. The value of NRS varied between 2 and 30 per 100 km 2 in the Pósa Valley when AE was changed to values between 0.5 and 2% (Figure 8).…”
Section: Discussioncontrasting
confidence: 56%
“…Note that our results differed from those of [2], in the way that NRS values change only slightly as a function of soil moisture content. According to [38], when based on field and statistical analyses, the number of monitoring stations can be optimized. In their field site the optimal number of monitoring station was found to be between 4 and 40 depending on saturation levels.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al, 2013); yet continuous observations of soil moisture dynamics of different ecosystems are still need to be strengthened . Knowledge of soil moisture is critical for developing an understanding of numerous hydrological processes in soil hydrology, meteorology, and ecology research (Brocca et al, 2010;Green and Erskine, 2004;He et al, 2012). Soil moisture is regarded as the basis of quantitative research on hydrological dynamics and ecological patterns/processes (Rodriguez-Iturbel, 2000), participating as crony in the terrestrial hydrological cycle across the "lithosphere-biosphere-atmosphere-hydrosphere" and affecting the growth and succession of vegetation.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found increases in the standard deviation (SD) of soil moisture with reductions in the mean moisture content (Brocca et al 2007;Hupet and Vanclooster 2002), while others have found the opposite (Famiglietti et al 1998;Martinez-Fernandez and Ceballos 2003). Recent studies have found that the SD and mean moisture content display a convex upward relationship (Brocca et al 2010;Gao et al 2011).…”
Section: Introductionmentioning
confidence: 99%